Underlying pathology of women with "atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion" smears, in a region with a high incidence of cervical cancer - Chumnan Kietpeerakool (2018)
Aim: To evaluate the histopathology of women who had "atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesions" (ASC-H) on cervical cytology in a region with high incidence of cervical cancer. Methods: This study was conducted at Chiang Mai University Hospital, Chiang Mai, Thailand. All women with ASC-H, who had undergone colposcopic and histolopathologic evaluation between October 2004 and January 2007, were recruited. Similar cohorts with other squamous cell abnormalities on a Pap-smear, who had undergone colposcopy during the same period, were included as comparative groups. Results: During the study period, 85 women who had ASC-H smears underwent colposcopic and histopathologic evaluation. The mean age was 45.3 years (range, 20-64 years). The histopathologic results of these 85 women were as follows: cervical intraepithelial neoplasia (CIN) II-III, 52 (61.2%); invasive cancer, 7 (8.2%); CIN I, 6 (7.1%); and no lesions, 20 (23.5%). The incidence of underlying CIN II or higher in an ASC-H smear (69.4%) was intermediate between atypical squamous cell of undetermined significance (22.7%), low-grade squamous intraepithelial lesion (44.7%) and high-grade squamous intraepithelial lesion (90.5%) smears. There was no statistically significant difference in the incidence of CIN II or higher between women who were 40 years old or more and those who were younger (68.7% and 71.4%, respectively, P = 0.81), or between pre-menopausal and post-menopausal women (71.4% and 63.6%, respectively, P = 0.49). Conclusion: Reporting ASC-H cytology in our population is strongly associated with significant cervical pathology, particularly invasive cancer that is possibly at a rate higher than previously reported. Women who have ASC-H smears should therefore be referred for immediate colposcopy regardless of age and menopausal status. © 2008 The Authors.